Freaky phenomena over 1,500 amazing and bizarre facts - Levy, Joel 1971- (Elwin Street Productions, 2010)
More than just a book of facts, figures, and lists, "Freaky phenomena" also contains anecdotes and stories of "weird or what?" people, animals, plants, food, weather, and the paranormal, and answers all the burning questions that arise from the weird phenomena in the universe
Includes index
Keywords: Curiosities and wonders